Novel Bioderived Composites from Wastes - Petrella, Andrea; Race, Marco; Spasiano, Danilo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The recovery of solid wastes for the preparation of innovative composite materials not only represents an economic advantage, but also offers an ecological opportunity for the utilization of by-products which would otherwise be landfilled. Specifically, the reuse and recycling of waste lead to important savings of raw materials and energy, since these by-products, generally deriv from agricultural or industrial activities, are abundant in nature. Moreover, a reduction of the environmental and related sanitary impacts can be also achieved. For this reason, a recycling operation is fundamental for the improvement of the environmental sustainability, because these secondary raw materials become a resource that can be easily reused without the modification of the peculiar characteristics, in order to obtain new and performing composites, with a low specific weight, high durability, and long life cycle.